Implementasi Dukungan Spiritual Berbasis Budaya Menurunkan Kecemasan pada Pasien Stroke - Ahmad Zaini Arif (Wiraraja Medika : Jurnal Kesehatan, 2020)
ABSTRACT Stroke is generally known as an attacking disease, crippling and even able to kill humans. Besides having physical and psychological problems, stroke patients also have psychospiritual problems. The aim of the study was to analyze the effect of Transcultural Theory (ISST) spiritual support implementation on the level of anxiety in Stroke Patients. The design of this study was Quasi-Experimental approach with pre post test control group design, the sample was 36 patients, divided into 2, treatment groups and controls were taken by simple random sampling technique. Data analysis using the t test with 2 free samples with α = 0.05. The results showed that the results of the difference in the anxiety level of the intervention group were ± (SD) = -4.61 ± (1.94) and the control group namely ± (SD) = 0.22 ± (3.38). The results of independent t test, P = 0.007, meaning that there is the effect of transcultural theory (ISST) spiritual support implementation on the level of anxiety. Giving Implementation of spiritual support based on transcultural theory (ISST) can reduce anxiety levels. Nurses can provide spiritual support based on transcultural theory (ISST) in stroke patients as an intervention in spiritual nursing care.